Optimasi Pelarut Ekstraksi, Aktivitas Anthelmintika terhadap Ascaris lumbricoides Suis., dan Telaah Fitokimia Bunga Ekor Kucing (Acalypha hispida Burm. F.) - MAMIK PONCO RAHAYU; ESTU SYA’BANA; AROFATUL HIDAYAH (Jurnal Farmasi Indonesia, 2012)
Red hot cat's tail (Acalypha hispida Burm. F.) flowers is a traditional medicinal plant which can be used as an antelmintic. The aim of present study was to determine the solvent extraction of Red hot cat's tail flowers that produce the highest yield, to determine antelmintic activity against roundworms (Ascaris lumbricoides Suis.) and to determine the compounds in the extract. The powder was extracted by maceration with ethanol with four variations concentration. Extract was analyzed the soluble in ethanol extract concentration and the yield. The highest yield extract was tested on roundworms by in vitro. The worms were grouped into 12 groups randomly without regard to gender. The group consists of one negative control group was be given distilled water, the positive control group was be given piperazine citrate in 5 different concentrations, and the red hot cat's tail flowers group with 6 variations of concentration. Observation of the worm is done after 24 hours of treatment. Data were analyzed by probit method to determine the LC50. The results of this study were solvent extraction that produces the highest yield was 70% ethanol. The 70% ethanol extract had an antelmintic activity against roundworms with 6,61% w/v as LC50 values that equivalent to 0,12% w/v piperazine citrate. The 70% ethanol extract contained saponins, flavonoids, and tannins.